A proposed clinical research support career pathway for noninvestigators. Issue 3 (8th March 2018) - Smith, Sheree; Gullick, Janice; Ballard, Jacqueline; Perry, Lin
Abstract: Aim: To discuss the international experience of clinical research support for noninvestigator roles and to propose a new pathway for Australia, to promote a sustainable research support workforce capable of delivering high‐quality clinical research. Background: Noninvestigator research support roles are currently characterized by an ad hoc approach to training, with limited role delineation and perceived professional isolation with implications for study completion rates and participant safety. A focused approach to developing and implementing research support pathways has improved patient recruitment, study completion, job satisfaction, and research governance. Data Sources: The Queensland and New South Wales state‐based Nurses' Awards, the Australian Qualifications Framework, and a University Professional (Research) Staff Award. Research nurses in the clinical environment improve study coordination, adherence to study protocol, patient safety, and clinical care. Conclusion: A career pathway that guides education and outlines position descriptions and skill sets would enhance development of the research support workforce. This pathway could contribute to changing the patient outcomes through coordination and study completion of high‐quality research. A wide consultative approach is required to determine a cost‐effective and feasible approach to implementation and evaluation of the proposed pathway. SUMMARY STATEMENT: What is already known about this topic? Noninvestigator research support roles are characterized by an ad hoc approach to training, a lack of role delineation, and professional isolation. A focused approach to developing, implementing, and evaluating research support pathways has improved patient recruitment, study completion rates, and research governance. What this paper adds? This discussion paper maps a tertiary professional research award to nursing industrial award levels and a higher education qualification framework, providing a blue print for education providers and industry. The implications of this paper: Provides an integrated professional pathway that recognizes the value and skill set of the research support role for high‐quality clinical research. Highlights the need for broad and consultative strategic engagement. Draws attention to government and professional bodies as key stakeholders in developing a set of minimum standards for research support training.